PENGEMBANGAN E-MODUL BERNUANSA GAYA BELAJAR UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI PERSAMAAN GARIS LURUS PESERTA DIDIK KELAS VIII SMP - Rahayu, Zelly Putri (Departemen Matematika, 2024)
Abstract - The purpose of this study was to create a valid, useful, and efficient e-module on straight line equations with nuanced learning styles for junior high school students in class VIII. This research is development research with the Plomp model which consists of 3 stages, namely preliminary research, development or prototyping phase, and assessment phase. The e-module based on learning styles was considered valid according to validation from five validators with a score of 84.81%. The practicality results received a score of 85,42% from students in the practical category and 90,83% from educators in the very practical category. As demonstrated by the rise in students' test results at every meeting throughout the small group assessment phase, e-modules are beneficial in enhancing problem solving skills. As a result, the constructed e-module with nuanced learning methods in the straight line equation content is reliable, useful, and capable of enhancing students' problem-solving skills.Keywords– E-Module, Mathematical Problem Solving,Nuanced Learning Styles